2014
DOI: 10.1155/2014/850126
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus pseudintermediusandStaphylococcus schleiferiSubspeciescoagulansfrom Canine Pyoderma Cases in Grenada, West Indies, and Their Susceptibility to Beta-Lactam Drugs

Abstract: Over a 2-year period 66 cases of canine pyoderma in Grenada, West Indies, were examined by aerobic culture in order to ascertain the bacteria involved and their antimicrobial resistance patterns. Of the 116 total bacterial isolates obtained, the majority belonged to Gram-positive species, and the most common organism identified through biochemical and molecular methods was Staphylococcus pseudintermedius. Additionally, identification of a Staphylococcus schleiferi subspecies coagulans isolate was confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
12
1
2
Order By: Relevance
“…Our studies revealed that most of the coagulase-positive staphylococci were susceptible to cephalothin and gentamicin and by comparison, the majority were resistant to neomycin. Not surprisingly, the susceptibility of staphylococci from dogs to cephalothin and gentamicin has previously been reported as relatively high in earlier studies ( 5 , 7 , 20 , 21 ). A high degree of resistance to neomycin was seen in this study, although there was no information implicating its routine use in the treatment of otitis externa.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our studies revealed that most of the coagulase-positive staphylococci were susceptible to cephalothin and gentamicin and by comparison, the majority were resistant to neomycin. Not surprisingly, the susceptibility of staphylococci from dogs to cephalothin and gentamicin has previously been reported as relatively high in earlier studies ( 5 , 7 , 20 , 21 ). A high degree of resistance to neomycin was seen in this study, although there was no information implicating its routine use in the treatment of otitis externa.…”
Section: Discussionmentioning
confidence: 79%
“…The relatively low occurrence of MRSP among staphylococci from dogs in this study (2 out of 65 isolates) is consistent with previous reports ( 27 , 28 ). Furthermore, a recent study in Grenada reported a lack of methicillin resistance in 28 isolates of S. pseudintermedius from cases of canine pyoderma ( 21 ). Indeed, MRSP has previously been detected at veterinary teaching hospitals ( 28 – 30 ), and evidence indicates that they can cause infections in humans ( 11 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…8,13,19 SIG includes 3 distinct species: Staphylococcus intermedius, Staphylococcus pseudintermedius, and Staphylococcus delphini. 1,14 The newest described species, S. pseudintermedius, is the most common cause of canine staphylococcal infections.…”
Section: Brief Communicationmentioning
confidence: 99%
“…Finally, dogs and cats are susceptible to different spectra of infectious diseases other than the arthropod-borne infections. For example, dogs are more commonly affected by bacterial pyoderma [ 71 ], leptospirosis [ 72 – 74 ] and systemic or non-invasive upper respiratory fungal infections [ 75 ] than cats, but cats are increasingly reported with mycobacterial infections [ 76 ] or invasive upper respiratory tract fungal infections [ 77 ]. Cats are much more often affected by a range of viral infections than dogs (e.g.…”
Section: Introductionmentioning
confidence: 99%